China’s Afghanistan Policy: Implications for Pakistan - Mr. Samran Ali (CISS Insight Journal, 2018)
China is growing from a regional to a global power. According to the power transition theory, the rise of China places it in a natural competition with the United States both economically and militarily. China’s economic interests stretch from its immediate neighborhood to other continents. It is also working on reviving the Old Silk trade route, which covers its western regions, and Central and South Asia. It is also investing heavily in these regions. States’ economic interests go alongside with their political interests. The Belt and Road Initiative (BRI), launched in 2013, and other economic ventures would, therefore, allow China to use soft power to shape the public opinion in several regions. China’s growing economic and political interests pose security challenges for it as well, which in turn demand a proactive foreign policy. The rivalry between the US and China is growing amid the US policy of Pivot to Asia and the alliance between Chinese regional rivals and the US. These factors are urging China to take measures for safeguarding its interests in the region and beyond. Although the US under President Trump has withdrawn from Trans-Pacific Partnership (TPP), its strategic objectives and policies in the region, crafted in the last few decades, have not changed i.e. ‘Japan as keystone,’ ‘India as counterweight’ and the regional alliance of democratic countries.